Domination and Resistance in Christianized Schooling in Amazon - Raimundo Nonato de Pádua Câncio; Sônia Maria da Silva Araújo (Universidade Federal do Rio Grande do Sul, 2021)
The aim of this study is to demonstrate how Christianized schooling, mobilized by American missionaries, was appropriated by the Waiwai indigenous people from Aldeia Mapuera, state of Pará, in the Brazilian Amazon. Methodologically, this is an ethnographic case study carried out in the Indigenous Territory Nhamundá-Mapuera in Pará, with teachers and indigenous people. At the theoretical level, data analysis is inspired by decolonial theory. The results show that the Waiwai did not passively accept the imposed process, despite understanding schooling as an irremediable value. Practices of domination and resistance, contradictorily, were being established and today they act as instruments of survival.